2017
DOI: 10.3389/fneur.2017.00387
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Imaging of Intracranial Atherosclerosis: Lessons from Interventional Cardiology

Abstract: Intracranial atherosclerosis is a major cause of ischemic stroke. Patients with a high degree of stenosis have a significant rate of stroke despite medical therapy. Two randomized trials of stenting have failed to show benefit. Improving periprocedural complication rates and patient selection may improve stenting outcomes. Fractional flow reserve (FFR), intravascular ultrasound (IVUS), and optical coherence tomography (OCT) are intravascular imaging techniques employed to improve patient selection and stent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…A growing body of pre-clinical evidence supports the premise that high-resolution cerebrovascular imaging, with the ability to assess vessel wall disease and neurovascular devices, will have a significant impact on the endovascular treatment of cerebrovascular disease [8][9][10]21,29,30 . Recently, it has been shown that in a leporine in vivo model the complete apposition of flowdiverting stents is critically important to achieve early and complete aneurysm occlusion, but histological evidence of poor apposition was not accurately captured on gold-standard DSA imaging 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of pre-clinical evidence supports the premise that high-resolution cerebrovascular imaging, with the ability to assess vessel wall disease and neurovascular devices, will have a significant impact on the endovascular treatment of cerebrovascular disease [8][9][10]21,29,30 . Recently, it has been shown that in a leporine in vivo model the complete apposition of flowdiverting stents is critically important to achieve early and complete aneurysm occlusion, but histological evidence of poor apposition was not accurately captured on gold-standard DSA imaging 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric microscopy with the ability to visualize neurovascular devices in their entirety and the vessel wall microstructure in vivo may have a profound impact in endovascular neurosurgery [8][9][10] . Endoscopic optical-imaging techniques, with a resolution approaching the micron scale and feasible incorporation in small fiber-optics probes, are a promising candidate for a successful translation to the clinic 11,12 .…”
mentioning
confidence: 99%
“…Endovascular intravascular ultrasound (IVUS) and optical coherence tomography (OCT) have recently been used in cerebral artery evaluation to determine plaque characteristics and composition, as well as perforator artery identification 4. More recently, OCT has shown to have better imaging characteristics than IVUS.…”
Section: Diagnosismentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) and optical coherence tomography (OCT, the light analog of IVUS) are intravascular imaging techniques used in interventional cardiology [ 48 ]. The results of several case reports suggest that these techniques may provide information for use in the selection of patients with intracranial atherosclerosis who may benefit from stent placement therapy [ 49 ]. These techniques could provide virtual histology to characterize the plaque in large intracranial vessels (distal ICA, VA, and basilar artery).…”
Section: Recent Advances In the Evaluation Of Iladmentioning
confidence: 99%